Estudos de afundamentos de tensão na expansão de sistemas elétricos: análise do parâmetro duração - Alyson Geraldo Guimaraes Cardoso (2011)
The occurrence of voltage sags directly influences the quality of the energy supplied by the electrical systems and generates losses for both consumers and power utilities. This work focuses the phenomenon from the expansion activity perspective in order to avoid or minimize its occurrence. The voltage sag duration time is the parameter that is mainly investigated. This research proposes a innovative weighting factor, named factor , that relates the actuation time of the protection system to the voltage sag duration time. Taking into account this factor, the performance index IALPLAN is presented and constitutes an improvement of the previous researches.